Linolenic acid-modified methoxy poly (ethylene glycol)-oligochitosan conjugate micelles for encapsulation of amphotericin B. (1st February 2019) - Song, Zhimei; Wen, Yi; Deng, Peizong; Teng, Fangfang; Zhou, Feilong; Xu, Hongmei; Feng, Sijia; Zhu, Li; Feng, Runliang
Graphical abstract: Highlights: Linolenic acid-modified methoxy poly(ethylene glycol)-chitosan conjugate was synthesized and applied to prepare amphotericin B-loaded micelles. Amphotericin B was encapsulated into the micelles with 82.27 ± 1.96 % of drug encapsulation efficiency and 10.52 ± 0.22 % of drug loading capacity. The amphotericin B-loaded micelles slowed down amphotericin B's release, reduced its side effects (hemolysis or renal damage) and improved its pharmacokinetic parameters. The drug-loaded micelles obviouly enhanced the cellular uptake of amphotericin B, showing antifungal activity equivalent to commercial amphotericin injection. Abstract: Introduction of linolenic acid (LNA) and methoxy poly (ethylene glycol) (MPEG) to the backbone of oligochitosan (CS) afforded LNA-modified MPEG-CS conjugate (MPEG-CS-LNA). Amphotericin B-loaded MPEG-CS-LNA micelles (AmB-M) were prepared via dialysis method with 82.27 ± 1.96% of drug encapsulation efficiency and 10.52 ± 0.22% of drug loading capacity. The AmB-M enhanced AmB's water-solubility to 1.64 mg/mL, being 1640-folds higher than native AmB. The AmB-M obviously reduced hemolytic effect and renal toxicity of AmB when compared to marketed AmB injection (AmB-I). Its antifungal activity against Candida albicans was equivalent to AmB-I although AmB's release from AmB-M was significantly retarded. According to fluorescence microscopy test, the unchanged activity should be attributed to enhanced fungal cellular uptake of AmB-M caused by combined inducement of LNA and CS. The pharmacokinetic studies demonstrated that AmB-M also improved the pharmacokinetic parameters of AmB with AmB-I as control. Conclusively, developed LNA-modified MPEG-CS micellar system could be a viable alternative to the current toxic commercial AmB-I as a highly efficacious drug delivery system.